Assessing global potential output growth: October 2020 - Xin Scott Chen; Ali Jaffery; Guillaume Nolin; Karim Salhab; Peter Shannon; Subrata Sarker (Bank of Canada, 2021)
This paper presents updated estimates of potential output growth for the global economy through 2022. Global potential output growth is expected to decline sharply in the aftermath of the COVID-19 pandemic and recover partially by the end of the projection horizon of the October 2020 Monetary Policy Report. More specifically, global potential output growth is expected to decline from 3.3 percent in 2019 to 2.1 percent in 2020 and then recover gradually to 2.7 percent by 2022. While growth is expected to decline in all regions, the negative effects of COVID-19 on trend labour productivity growth in emerging market economies are the largest contributor to the overall expected slowdown in global growth. This also reflects Bank of Canada staff's assessments of ongoing headwinds from aging, trade tensions and structurally low trend total factor productivity growth across all regions. A partial recovery in all regions is expected to be driven mainly by the gradual recovery in trend total factor productivity growth and trend labour input growth. In the US, potential output growth is expected to decline sharply in 2020, mostly due to a decline in the trend participation rate and a reduction in the growth rate of immigration. By 2022, US potential output growth is expected to partially recover due to an improvement in trend total factor productivity growth and a modest recovery in trend labour input growth.
Keywords: E10; E20; O4; 330; Potential output; Productivity